1992
DOI: 10.1007/bf02012489
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler imaging of intracranial vasculopathy in severe infantile sialidosis

Abstract: Neonatal ascites is usually attributed to prenatal infections, lysosomal storage disease and anomalies of the genitourinary tract, gastrointestinal tract or cardiovascular system. We report one case of neonatal ascites associated with infantile sialidosis. Cerebral sonography showed stripe-like intracerebral echogenicities in the region of the basal ganglia. Colour Doppler imaging demonstrated blood flow within the echogenicities confirming the suspected diagnosis of intracranial vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…It can be observed that hydrops, ascites, and edema are the distinguishing features of the severe, congenital group of the disease, followed by coarse features, dysostosis multiplex, and hepatosplenomegaly. Renal involvement, cardiac anomalies, ophthalmic finding, myoclonus, inguinal hernia, telangiectasias, petechiae, bluish to purpuric macules and hydrocephalus are the clinical features that may infrequently manifest [ 9 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Studies reporting histopathological features of congenital sialidosis are limited.…”
Section: Morphological and Clinical Aspects Of Sialidosis And mentioning
confidence: 99%
“…It can be observed that hydrops, ascites, and edema are the distinguishing features of the severe, congenital group of the disease, followed by coarse features, dysostosis multiplex, and hepatosplenomegaly. Renal involvement, cardiac anomalies, ophthalmic finding, myoclonus, inguinal hernia, telangiectasias, petechiae, bluish to purpuric macules and hydrocephalus are the clinical features that may infrequently manifest [ 9 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Studies reporting histopathological features of congenital sialidosis are limited.…”
Section: Morphological and Clinical Aspects Of Sialidosis And mentioning
confidence: 99%
“…Echogenitä tsvermehrungen werden zwar hä ufig nach prä natalen Infektionen gefunden, sind jedoch hierfü r nicht spezifisch, da sie auch bei einer Trisomie 13 und bei Stoffwechselerkrankungen beschrieben wurden [3,5,25,26,28,37].…”
Section: Diskussionunclassified
“…1 4 5 8 Histopathological examination shows that most lenticulostriate arteries involved in LSV are medium sized, have thickened and hypercellular walls without fibrosis or hyalinisation, but with intramural and perivascular deposition of amorphous basophilic material, iron, and calcium, 4 5 9 and signs of vessel wall damage. 4 Since the initial description of LSV by Grant et al 10 in 1985, more than 25 reports of neonatal LSV have been published, in which LSV appeared to be associated with a variety of congenital and acquired neonatal conditions, such as fetal and neonatal infections, mainly cytomegalovirus, 1-4 6-9 11-15 chromosomal aberrations, 2-4 6 8 9 16 17 hypoxic/ischaemic conditions, [4][5][6] congenital heart disease, 4 fetal alcohol or drug exposure, [3][4][5][6] congenital malformations, 1 4 6 neonatal lupus erythematosus, 3 6 twin to twin transfusion, 18 sialidosis, 19 hydrops fetalis, 6 and diabetic fetopathy. 1 Most published reports of LSV are either of large retrospective studies [2][3][4][5][6][7] or are case reports, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] except for one prospective study by Kriss et al 8 in w...…”
mentioning
confidence: 99%